PENGARUH AKUNTABILITAS, PENGETAHUAN, PENGALAMAN, DAN INDEPENDENSI TERHADAP KUALITAS HASIL KERJA AUDITOR (Studi Empiris pada KAP di Kota Semarang dan Surakarta) - Bella Ariviana; Haryanto Haryanto (Diponegoro Journal of Accounting, 2014)
This research was aimed to empirically analyze the influence of accountability, knowledge, experience, and independence to the quality of the work of the auditor. This research was conducted in Central Java with the respondent auditor who worked in public accountant office in Semarang and Surakarta. The samples were conducted by purposive judgment sampling technique. Data was collected using questionnaires distributed as much as 70 and only 56 questionnaires can be processed. Data analysis using multiple linear regression analysis. The results showed that accountability, knowledge, experience, and independence has a positive influence on the quality of the work of the auditor.